“If I forget you Jerusalem” (Ps. 137:4). The Transmission of Sacred Discourse in the Bible and in African Indigenous Sacred Texts - M.K. Mensah (Acta Theologica)
African biblical scholars have long advocated a shift in existing exegetical and hermeneutical approaches. The reasons include not simply the inadequacy of these approaches in dealing with the existential questions of contemporary African societies, but also their lack of effectiveness in transmitting the results of the exegetical process to receptor cultures in Africa, partly to be blamed on their colonialist legacy. One pathway to resolving the above challenge, which remains insufficiently explored, is to engage in a dialogue between the biblical text and African indigenous sacred texts. This paper, using a dialogical approach of African biblical hermeneutics, brings Psalm 137 into dialogue with the Adinkra amammere (tradition), an indigenous text of the Akan of Ghana. It argues that reading these texts together uncovers their complementary views on the preservation and transmission of sacred discourse and could facilitate reception of the biblical message in contemporary Ghanian society.